Edukasi Perencanaan Masa Depan berdasarkan Yakobus 4:13-15 bagi Murid PPA Efrata ID0524 di Loa Kulu, Kutai Kertanegara - Paulus Dimas Prabowo (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
Adolescence is a crucial period in determining the future. Career is the most important thing to think about and plan. A teenager not only needs to have careful calculations but also receive guidance from more senior people in planning his future. This research focuses on educational efforts for future planning based on James 4:13-15 for PPA Efrata ID0524 students in Loa Kulu, Kutai Kertanegara. This activity aims to provide a biblical understanding of future planning so that PPA Efrata ID0524 students get encouragement to plan well for the future. Reporting of PkM results is carried out using a qualitative approach, presented descriptively, and supported by literature studies and activity documentation. As a result, the participants who were still teenagers gained an understanding of the encouragement to plan for the future in accordance with the principles contained in James 4:13-15, namely: first, future plans need to be prepared in detail (v. 13); second, planning for the future requires awareness of one's limitations (v. 14); third, planning for the future must be according to divine will (v. 15).